2014
DOI: 10.1152/ajpcell.00383.2013
|View full text |Cite
|
Sign up to set email alerts
|

Collagen content does not alter the passive mechanical properties of fibrotic skeletal muscle in mdx mice

Abstract: Many skeletal muscle diseases are associated with progressive fibrosis leading to impaired muscle function. Collagen within the extracellular matrix is the primary structural protein providing a mechanical scaffold for cells within tissues. During fibrosis collagen not only increases in amount but also undergoes posttranslational changes that alter its organization that is thought to contribute to tissue stiffness. Little, however, is known about collagen organization in fibrotic muscle and its consequences fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
163
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(181 citation statements)
references
References 52 publications
(72 reference statements)
14
163
1
3
Order By: Relevance
“…Fibrosis is a final result of a chronic inflammatory process on dystrophic muscle due to the absence of dystrophin (Smith & Barton;Fontana et al, 2015). We have shown that this modality and intensity of training affected the intramuscular fibrosis in a beneficial way but further investigations are required to explain if LIT has delayed the formation of an intramuscular fibrosis or if it was reorganized by the contraction-induced adaptations on skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 91%
“…Fibrosis is a final result of a chronic inflammatory process on dystrophic muscle due to the absence of dystrophin (Smith & Barton;Fontana et al, 2015). We have shown that this modality and intensity of training affected the intramuscular fibrosis in a beneficial way but further investigations are required to explain if LIT has delayed the formation of an intramuscular fibrosis or if it was reorganized by the contraction-induced adaptations on skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 91%
“…The use of a mathematical model with realistic healthy and pathological connective tissue properties enables us to determine that the increased resistance to radial expansion reduces a muscle capacity to generate work independent of any other changes. Remodeling of the ECM with age (Ramaswamy et al 2011) and disease (Smith and Barton 2014) is often associated with an increase in collagen content (as a proportion of the cross section) and in turn a large decreases in specific force. Therefore, muscles with increased collagen content likely face both a reduction in specific force and shortening capacity, such that the mechanical work output is potentially more compromised than our results indicate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed us to input into the model empirical data from studies that have quantified the relative proportion of a muscle cross section that is composed of collagen/ECM versus contractile muscle cells with values ranging from 2 to 20% (Lieber and Ward 2013; Smith and Barton 2014; Wood et al 2014). In addition, our simulations allowed us to vary the initial orientation of collagen fibers to explore the effect of collagen pitch angle on collagen strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while proven histology approaches for both collagen 83,84 and Eln 85,86 are more inclusive of fiber types, they require fixation and potentially physical sectioning before staining, obviating the application of these methods to live samples and limiting the 3D assessment of the microenvironments. Although SHG and MPLSM, in their current form, have limitations, overcoming these deficiencies is the focus of ongoing work by several groups.…”
Section: Discussionmentioning
confidence: 99%